2008
DOI: 10.1016/j.heares.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signaling in the inner ear

Abstract: Epithelial cells of the inner ear coordinate their ion transport activity through a number of mechanisms. One important mechanism is the autocrine and paracrine signaling among neighboring cells in the ear via nucleotides, such as adenosine, ATP and UTP. This review summarizes observations on the release, detection and degradation of nucleotides by epithelial cells of the inner ear. Purinergic signaling is thought to be important for endolymph ion homeostasis and for protection from over stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Above findings indicate that the signalling pathways from P2Y2 (or P2Y4) receptors that modulate K + channels might be different to those modulating Cl À channels. It has been suggested that phophatidylinositol 4,5 biphosphate (PIP2) is an important regulator of KCNQ channels and its depletion reduces the channel activity (Loussouarn et al 2003, Zhang et al 2003, Park et al 2005, Lee & Marcus 2008. This may explain our findings that show a decrease in KCNQ1 currents by the P2Y2 receptor co-expression.…”
Section: Effect Of P2y2 and Adenosine Receptors On Currentssupporting
confidence: 57%
See 1 more Smart Citation
“…Above findings indicate that the signalling pathways from P2Y2 (or P2Y4) receptors that modulate K + channels might be different to those modulating Cl À channels. It has been suggested that phophatidylinositol 4,5 biphosphate (PIP2) is an important regulator of KCNQ channels and its depletion reduces the channel activity (Loussouarn et al 2003, Zhang et al 2003, Park et al 2005, Lee & Marcus 2008. This may explain our findings that show a decrease in KCNQ1 currents by the P2Y2 receptor co-expression.…”
Section: Effect Of P2y2 and Adenosine Receptors On Currentssupporting
confidence: 57%
“…The strial marginal cells and vestibular dark cell of the inner ear of rodents express KCNQ1, its auxiliary b-subunit KCNE1 and purinergic receptors (P2Y4) at the apical membrane, and these receptor/channel proteins seem to have an important function in endolymph homeostasis and protection from overstimulation (Lee & Marcus 2008, Housley et al 2009). KCNQ1/KCNE1 channel activity and thus K + secretion are down-regulated by several purinergic pathways in rodents including the P2Y4 receptors (Lee & Marcus 2008). In mouse cardiomyocytes and oocyte expression system, P2 receptors up-regulate KCNQ1/KCNE1 channel activity (Honore et al 1992).…”
Section: Effect Of P2y2 and Adenosine Receptors On Currentsmentioning
confidence: 99%
“…55,56 Furthermore, extracellular ATP is recognized as an important autocrine/paracrine signal molecule that participates in the regulation of several cellular functions. [57][58][59][60][61] Interestingly, ATP is released from dying tumor cells by exposure to several cell death inducers. 55,62 Recent studies have identified tumor-derived ATP as a new damage-associated molecular pattern, being necessary for cancer cell death to be immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…There are several recent reviews focused on purineric regulation of epithelia of the kidney (Rieg & Vallon 2009, Praetorius & Leipziger 2010), gastrointestinal tract (Christofi 2008), pancreas and salivary glands (Novak 2003, 2008), tear secretions (Crooke et al. 2008), airway epithelia (Davis & Lazarowski 2008, Lazarowski & Boucher 2009) and inner ear (Lee & Marcus 2008). In the following paragraphs, I will adopt the integrative approach to purinergic regulation of ion channels/transporters, and highlight common elements and differences that underlie the basics of epithelial secretion and absorption.…”
Section: Effect Of Purinergic Signalling On Ion Transportmentioning
confidence: 99%
“…For example, ATP inhibits: KCNQ1 channels in vestibular dark cells of the inner ear (via P2Y4 receptors; Marcus et al. 1997, Lee & Marcus 2008), M‐type K + currents in sympathetic neurons (via P2Y1; Filippov et al. 1998, 2004, 2006), GIRK channels (Mark et al.…”
Section: Effect Of Purinergic Signalling On Ion Transportmentioning
confidence: 99%